Effect of nutrient management practices and cropping systems on organic production of crops - PRADHAN, ADIKANT; MALAIYA, S; AGRAWAL, S; NAYAK, V; DIXIT, ANIL; AMARNATH; MOHAPATRA, SWEEKRUTA (The Indian Journal of Agricultural Sciences, 2026)
A study was carried out during 2022, 2023 and 2024 under All India Coordinated Research Project on Integrated Farming System at Instructional cum Research Farm, Indira Gandhi Krishi Vishwavidyala, Raipur, Chattisgarh in strip plot design (SPD) with three replications. The treatment combinations included nutrient management practices, viz. 100%, 50% and 25% nutrients through inorganic and organic sources with combination of beejamrit, ghanjeevamrit, jeevamrit; and four cropping systems, viz. soybean [Glycine max (L.) Merr.], sweet corn [Zea mays (L.) Saccharata], French bean (Phaseolus vulgaris L.), cabbage (Brassica oleracea var. capitata L.) and tomato (Solanum lycopersicum L.). Soybean–tomato recorded the highest total productivity (570.2 q/ha) with NM6. Application of 100% N through inorganic sources + 5 t FYM resulted greater uptake of available N (26.51 kg/ha) and available P (23.44 kg/ha) along with higher organic carbon (0.79%), whereas available K was higher (415.8 kg/ha) with 25% organic + 25% inorganic sources + Natural farming. Soybean–tomato was more economically feasible system under NM1 in gross (₹4,32,201/ ha) and net (₹3,38,259/ha) returns.